2018
DOI: 10.1016/j.celrep.2018.07.076
|View full text |Cite
|
Sign up to set email alerts
|

Joint Representation of Spatial and Phonetic Features in the Human Core Auditory Cortex

Abstract: The human auditory cortex simultaneously processes speech and determines the location of a speaker in space. Neuroimaging studies in humans have implicated core auditory areas in processing the spectrotemporal and the spatial content of sound; however, how these features are represented together is unclear. We recorded directly from human subjects implanted bilaterally with depth electrodes in core auditory areas as they listened to speech from different directions. We found local and joint selectivity to spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…To test whether the sound-induced high-γ conform to a certain spatial distribution in either insular or supra-temporal areas, we calculated the Pearson correlation between the contact-level activations and latencies and their MNI coordinates, respectively. As shown in Figure 1E, a high-to-low gradient for activation and an early-to-late gradient for latency along the medial-lateral axis was found on the supra-temporal plane (HG, pSTG, and mSTG) (both p < 0.001), consistent with previous literature (Nourski et al, 2014;Patel et al, 2018). While in the InsP, a low-to-high gradient for activation a late-to-early gradient for latency along the anterior-posterior axis was found (both p < 0.001), consistent with the findings in non-human primates (Remedios et al, 2009).…”
Section: Auditory Functions In Human Insulasupporting
confidence: 91%
See 2 more Smart Citations
“…To test whether the sound-induced high-γ conform to a certain spatial distribution in either insular or supra-temporal areas, we calculated the Pearson correlation between the contact-level activations and latencies and their MNI coordinates, respectively. As shown in Figure 1E, a high-to-low gradient for activation and an early-to-late gradient for latency along the medial-lateral axis was found on the supra-temporal plane (HG, pSTG, and mSTG) (both p < 0.001), consistent with previous literature (Nourski et al, 2014;Patel et al, 2018). While in the InsP, a low-to-high gradient for activation a late-to-early gradient for latency along the anterior-posterior axis was found (both p < 0.001), consistent with the findings in non-human primates (Remedios et al, 2009).…”
Section: Auditory Functions In Human Insulasupporting
confidence: 91%
“…The human auditory cortex was more responsive to sounds coming from the Auditory functions in human insula contralateral directions (Ackermann et al, 2011;Patel et al, 2018). However, whether the InsP also has lateral selectivity is still unclear.…”
Section: Contralateral Dominancementioning
confidence: 99%
See 1 more Smart Citation
“…It . https://doi.org/10.1101/475673 doi: bioRxiv preprint research (Bednar and Lalor, 2018;Patel et al, 2018;Wolbers et al, 2011) has shown that the direction of auditory attention is neurally encoded, indicating that it could be possible to decode the attended sound position or trajectory from EEG. Especially the alpha power activity could be tracked to determine the locus of auditory attention (Frey et al, 2014;Haegens et al, 2011;Wöstmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This has been investigated based on differences in the EEG entropy features (Lu et al, 2018), but the performance was insufficient for practical use (below 70 % for 60 s windows). However, recent research Lalor, 2018, 2020;O'Sullivan et al, 2019;Patel et al, 2018;Wolbers et al, 2011) has shown that the direction of auditory attention is neurally encoded, indicating that it could be possible to decode the attended sound position or trajectory from EEG. Especially the alpha power activity could be tracked to determine the locus of auditory attention (Frey et al, 2014;Wöstmann et al, 2016), though those studies employed MEG.The aim of this paper is to further explore the possibilities of CNNs for EEG-based AAD.…”
mentioning
confidence: 99%